KOMBINASI JERAMI DAN AMPAS TEBU SEBAGAI BIOFOAM HIGH DURABILITY DAN WATERPROOF DENGAN METODE MIXING DAN MOLDING - Aulia Della Cornellia; Naura Aqillafasya Ashifa; Avilyan Fahrudin Churmelia; Zidan Sandy Rosyadi Al Fikri; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
The increasing use of styrofoam can certainly cause damage to the environment. From these problems it can be concluded that the use of styrofoam can be replaced with biofoam which is far more easily degraded and environmentally friendly. Straw and bagasse wastes have the potential to become biofoam raw materials because these two materials contain cellulose which is easily degraded. The method used in the manufacture of biofoam is mixing between mashed bagasse, straw, and tapioca flour. Then do the addition of PVA (Polyvynil Alcohol) as a waterproof agent. After everything is homogeneous, molding and heating are carried out at 1000 C for 60 minutes to remove the moisture content. The biofoam that is formed even though PVA has been added still has a high water absorption rate. This is because biofoam which has a starch base material is generally easy to interact with water so that the water content contained in biofoam is higher than commercial biofoam. However, biofoam can be more easily degraded due to the presence of water attached to or absorbed in the sample, making it easier for microorganisms to decompose. The use of styrofoam which causes damage to the environment is one of the reasons for replacing styrofoam with environmentally friendly materials, namely biofoam with the main ingredients being straw waste, bagasse, and added PVA using the mixing and molding method. Biofoam will replace the easy use of Styrofoam. Keywords : biofoam, straw, bagasse